Alterations in multidimensional motor unit number index of hand muscles after incomplete cervical spinal cord injury - Li, Le; Li, Xiaoyan; Liu, Jie; Zhou, Ping (Frontiers in Human Neuroscience, 2015)
The objective of this study was to apply a novel multidimensional motor unit number index (MD-MUNIX) technique to examine hand muscles in patients with incomplete cervical spinal cord injury (SCI). The MD-MUNIX was estimated from the compound muscle action potential (CMAP) and different levels of surface interference pattern electromyogram (EMG) at multiple directions of voluntary isometric muscle contraction. The MD-MUNIX was applied in the first dorsal interosseous (FDI), thenar and hypothenar muscles of SCI (n=12) and healthy control (n=12) subjects. The results showed that the SCI subjects had significantly smaller CMAP and MD-MUNIX in all the three examined muscles, compared to those derived from the healthy control subjects. The multidimensional motor unit size index (MD-MUSIX) demonstrated significantly larger values for the FDI and hypothenar muscles in SCI subjects than those from healthy control subjects, whereas the MD-MUSIX enlargement was marginally significant for the thenar muscles. The findings from the MD-MUNIX analyses provide an evidence of motor unit loss in hand muscles of cervical SCI patients, contributing to hand function deterioration.